Maternity Care Services in Different Countries - Kõosaar, Eliise; Kaasik-Aaslav, Urve; Siimer, Õilme; Kotkas, Ene (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Background: In the 21st century, it became common that people move from one country toanother with the intentions of settling permanently or temporarily in the new location. At thesame time, the number of asylum applicants and refugees is increasing in Europe. Forexample, based on data from 2014, 302 772 Ukrainian, 169 657 Chinese, 134 881 Indian andmore than 75 000 Syrian citizens have got residence permits. 44,1 million (6%) of Europeangeneral population are Muslims.This requires culturally sensitive midwifery and maternity care provided by healthprofessionals to a woman giving birth, knowledge of different religious beliefs and skills tosolve ethical problems caused by communication with patients having different cultural andreligious needs.Objective: To develop a literature review about maternity care in Syria, Turkey, China, Israel,India, Afghanistan and Ukraine.Methods: Qualitative research method has been used, a literature review has been developed.Conclusions: In different countries, people believe in various birth rituals and it is oftenwhen maternity care is provided by an attendant having no special training.For instance, in China, women giving birth are not recommended to be touched and careproviders have to give a reason for each touch. In India, a thing helping protect against the„evil eye“ has to be in a delivery room. Women in Eastern Turkey feel embarrassed at beingnaked during childbirth, especially when care is provided by a male one, and mostly thewomen give birth at home.According to Turkish beliefs, the sacred book Quran has to be in the room where a womangiving birth is. In Afganistan, in order to have midwifery care, the husband`s or some malerelative`s permission is required. In Syria, women often are not satisfied by forced measuresin maternity care services, for instance enema is given before labour, and having any directindications, labour induction is done.Health care services for all citizens in Ukraine are free ofcharge. Mostly, women give birth in hospitals where routine procedures are performedaccording to orders of personnel, ignoring wishes of women giving birth.Today, in these countries maternity care services in health care institutions are providedunder instruction of experienced personnel. Thus, culturally appropriate maternity care isexpected, if possible.